The Importance of The Black Sea Region in The Politics of the Bulgarian Government from The Unification Day to Bulgaria’s involvement in The First World War - Георгиев, Бисер (Дриновський збірник, 2020)
The problem concerning the strategic importance of the Black sea region is an old problem and at the same time an extremely contemporary one. It has been studied by various specialists working in different fields (military experts, historians, sociologists, political scientists, ethnologists, environmentalists, etc.). Every one of them has contributed to the development of this subject. Although there are still many aspects which haven’t been thoroughly clarified. One of them is the one regarding the attitude of each bulgarian politician and government between the years 1885−1915 when it comes to the Black sea’s export and the problems and perspectives bound with that option. This is the theme of the following report. The period from The Unification Day to the beginning of the First Worlds War was deliberately chosen because, not only the majority of the ports and facilities have been built during this time as well as the creation of the Bulgarian Black sea fleet,but at the same time different parties and politicians don’t share the same opinions regarding specific problems resulting in the creation of different concepts.Materials from central and provincial archive repositories have been used (Varna and Shumen for the most part), the National Assembly’s stenographic logs,the bulgarian periodic press,some foreign issues and contemporaries’ memoirs have been used in the creation of this scientific research. The achievments of the specialists until now has been reported.